Synthesis and Antitumor Evaluation of Menthone-Derived Pyrimidine-Urea Compounds as Potential PI3K/Akt/mTOR Signaling Pathway Inhibitor - Huang, Mei; Duan, Wengui; Chen, Naiyuan; Lin, Guishan; Wang, Xiu (Frontiers in Chemistry, 2022)
A series of novel menthone derivatives bearing pyrimidine and urea moieties was designed and synthesized to explore more potent natural product-derived antitumor agents. The structures of the target compounds were confirmed by FTIR, NMR, and HRMS. The in vitro antitumor activity was tested by standard methyl thiazolytetrazolium assay and showed that 4i, 4g, 4s, and 4m are the best compounds with IC50 values of 6.04 ± 0.62µM, 3.21 ± 0.67µM, 19.09 ± 0.49µM, and 18.68 ± 1.53µM, against Hela, MGC-803, MCF-7, and A549, respectively. The results of the preliminary action mechanism studies showed that compound 4i, the representative compound, could induce cell apoptosis in Hela cells in a dose-dependent manner and might arrest the cell cycle in the G2/M phase. Furthermore, the results of network pharmacology prediction and Western blot experiments indicated that compound 4i might inhibit Hela cells through inhibit PI3K/Akt/mTOR signaling pathway. The binding modes and the binding sites interactions between compound 4i and the target proteins were predicted preliminarily by the molecular docking method.